Union Leaders and the Economic Crisis : Responses to Restructuring - Pupo, Norene; White, Jerry (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1994)
The restructuring of the Canadian economy continued throughout the recession of the early 1990s. How do union leaders see this situation and what are their reactions ? We discuss the current economic restructuring, examining the "competitiveness" analysis of Michael Porter, the initiatives of capital and the state, such as the FTA and NAFTA, and the restructuring of the workplace through "flexibility initiatives". We explore the response of the unions to this complex situation as seen through the eyes of selected leaders and draw some tentative conclusions on the future directions of labour in Canada.